Analyzing Students’ Creative Thinking Skills Based on Rational and Guardian Personality Types - Anastasyia, Neneng; Sofyan, Abdul (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Differences in personality types significantly influence individuals’ ways of thinking, which in turn affect the problem-solving strategies they employ in mathematics. This study aims to analyze students’ Creative Thinking Ability (CTA) in solving mathematical problems based on rational and guardian personality types. A descriptive qualitative approach was employed, involving four tenth-grade students from SMA Negeri 2 Enrekang, consisting of two students with rational personality types and two with guardian personality types. The research instruments included a creative thinking ability test, the Keirsey personality test questionnaire, and interview guidelines. Data validity was ensured through source triangulation, while data analysis was carried out using data reduction, data display, and conclusion drawing. The findings revealed that students with rational personality types demonstrated higher levels of creative thinking ability, averaging at CTA level 3, as they were able to meet the indicators of fluency and flexibility in solving problems. However, both personality types did not show evidence of originality. Students with guardian personality types generally performed at CTA level 1, as they typically relied on a single method of problem-solving, except in problem number 2 where they were able to reach CTA level 3. This study was limited to rational and guardian personality types, and therefore cannot be generalized to other personality types. Future research is recommended to include artisan and idealist personality types to provide a more comprehensive understanding in line with David Keirsey’s theory.